Implikasi Hukum Terhadap Perjanjian Jual Beli Photocard yang Mengandung Unsur Penipuan (Bedrog) di Media Sosial X - Jagad Rahma Widanti; Arief Suryono (Lembaga Pengembangan Kinerja Dosen, 2025)
The phenomenon of buying and selling photocards is growing among music fans, with X social media widely chosen as a platform for buying and selling due to its ease of access and wide reach. However, this practice often raises legal issues, especially regarding the occurrence of fraud by the seller through the provision of false evidence of goods or the sale of non-original goods. This study aims to analyze the legal implications of photocard sale and purchase agreements that contain elements of fraud. This study uses a normative legal research method with a statutory approach and a conceptual approach. Based on the results of the research, it is known that the agreement containing elements of fraud does not fulfill the subjective aspects in the validity of the agreement as stipulated in the Civil Code (KUHPerdata), thus causing a defect of will. As a result, the agreement can be canceled through the mechanism of requesting cancellation in court.